Identifying the Factors that Contribute to Involuntary Departures of School Superintendents in Rural America - Robert J. Tekniepe (Journal of Research in Rural Education, 2015)
Rural school districts play an important part in the national educational landscape. Not only do they provide nearly one in four U.S. children with many skills, including those needed to enter college, but they also act as an economic stabilization force for the communities that they serve. Superintendents of rural school districts, as the leaders of these institutions, play an important role in fostering these objectives. Rapidly changing political, social, and economic landscapes, however, present a new array of challenges and occupational pressures to today's rural superintendent. Superintendents now must navigate more turbulent environments shaped by the ever-increasing demands of internal and external stakeholders in an era of tight fi scal constraints. Few studies have attempted to link the occupational pressures faced by rural school superintendents with ways in which these pressures increase the probability of a superintendent's experiencing an involuntary departure. This study attempts to fi ll that gap. Using data compiled from 618 rural superintendents across 48 states, this study shows that political confl ict, insuffi cient employment contract provisions, internal and external stakeholder pressures, and fi scal stress can affect rural school superintendent turnover.